An additive for inhibiting polyphosphoric acid crystallization and a method for preparing the same

CN122998778APending Publication Date: 2026-10-30XIANGYANG GAOLONG PHOSPHORUS CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611171646.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

晶体析出会造成输送管路堵塞、设备结垢沉积,同时大幅降低聚磷酸体系的有效利用率,导致水溶肥肥效衰减、阻燃体系防护性能下降

Benefits of technology

本发明能提供一种用于抑制聚磷酸结晶的添加剂及其制备方法,通过硼改性交联磷酸化聚准轮烷与磺基甜菜碱两性离子助稳剂的协同配伍,构建多重结晶抑制体系,突破传统抑制剂单一阻晶的技术瓶颈。硼改性交联结构形成稳定的三维滑移骨架,可动态适配聚磷酸晶面生长状态,持续钝化晶面活性,从源头抑制晶体发育。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998778A_ABST
    Figure CN122998778A_ABST
Patent Text Reader

Abstract

The application discloses an additive for inhibiting polyphosphoric acid crystallization and a preparation method thereof, relates to the technical field of polyphosphate aqueous solution stabilizers, and comprises the following components in parts by weight: boron-modified cross-linked phosphonated poly-prato-racahane 6-22 parts, an amphiphilic copolymer containing phosphatidylcholine block 2-8 parts, a sulfobetaine zwitterionic stabilizing aid 0.5-3 parts, and deionized water 67-91.5 parts. The application breaks through the technical bottleneck of traditional inhibitors in single crystal inhibition by constructing a multiple crystal inhibition system through the synergistic compatibility of the boron-modified cross-linked phosphonated poly-prato-racahane and the sulfobetaine zwitterionic stabilizing aid. The stable three-dimensional sliding skeleton formed by the boron-modified cross-linked structure can dynamically adapt to the crystal face growth state of polyphosphoric acid, continuously passivates the crystal face activity, and inhibits the development of the crystal from the source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyphosphate aqueous solution stabilizers, and in particular to an additive for inhibiting polyphosphate crystallization and its preparation method. Background Technology

[0002] Ammonium polyphosphate and other polyphosphate aqueous solutions are widely used in agricultural water-soluble fertilizers and industrial flame retardants. These aqueous solutions are supersaturated metastable systems, which are highly susceptible to temperature fluctuations, standing time, and ionic environment during normal storage and transportation. This causes spontaneous crystal nuclei to form and crystals to precipitate. Crystal precipitation can lead to blockage of pipelines, scaling and deposits on equipment, and a significant reduction in the effective utilization rate of the polyphosphate system, resulting in decreased fertilizer efficacy of water-soluble fertilizers and reduced protective performance of flame retardant systems.

[0003] Currently, the commonly used crystallization inhibition media in the industry are mostly polycarboxylate or small molecule phosphate inhibitors. These inhibitors can only temporarily inhibit crystal growth through a single surface adsorption mechanism, resulting in a limited functional mode and poor adaptability. Under long-term static and temperature-fluctuating conditions, their adsorption stability is insufficient, and they are prone to desorption failure. They cannot continuously inhibit crystal nucleation and crystal agglomeration, making it difficult to meet the practical application requirements for long-term storage and stable transportation of polyphosphate aqueous solutions, and exhibiting significant technical limitations. Summary of the Invention To address the aforementioned technical problems, this invention provides an additive for inhibiting polyphosphoric acid crystallization and a method for preparing the same. The technical solution is as follows: An additive for inhibiting polyphosphoric acid crystallization, comprising, by weight, the following components: 6-22 parts of boron-modified crosslinked phosphorylated polyrotaxane, 2-8 parts of an amphiphilic copolymer containing phosphocholine blocks, 0.5-3 parts of sulfobetaine zwitterionic stabilizer, and 67-91.5 parts of deionized water. The phosphorylated polyquasi-rotaxane is a polyanionic slip ring compound with sliding elasticity obtained by ring encapsulation of α-cyclodextrin and polyethylene glycol chains, followed by end-capping and partial phosphorylation modification. The amphiphilic copolymer containing the phosphocholine block is a copolymer with an AB block structure, wherein the A block is poly(2-methacryloyloxyethyl phosphocholine) and the B block is poly(oligomeric polyethylene glycol methyl ether methacrylate). The sulfobetaine zwitterionic stabilizer is used to shield the solution charge, enhance hydration and water retention, and synergistically inhibit the formation of polyphosphate crystal nuclei and crystal growth.

[0004] Optionally, the boron-modified crosslinked phosphorylated polyquadrane satisfies the following parameters: the number-average molecular weight of polyethylene glycol is 3000-8000, the molar ratio of α-cyclodextrin to the repeating ethylene oxide unit in polyethylene glycol is 1:2-1:4, the degree of phosphorylation substitution of α-cyclodextrin is 1.0-2.5, and the degree of boron crosslinking is 15%-30%.

[0005] Optionally, the amphiphilic copolymer containing the phosphocholine block satisfies the following parameters: the mass ratio of poly(2-methacryloyloxyethyl phosphocholine) block to poly(oligoethylene glycol methyl ether methacrylate) block is 1:2 to 2:1, the number-average molecular weight of the copolymer is 8000 to 30000, and the critical micelle concentration is 0.02 g / L to 0.08 g / L.

[0006] Optionally, the sulfobetaine zwitterionic stabilizer is N-sulfopropyl-N,N-dimethylbetaine, with a purity of ≥98%, a water solubility of ≥500g / L at 25℃, and stable existence in aqueous solutions with pH values ​​of 4–9 while maintaining its zwitterionic structure.

[0007] Optionally, the pH value of the additive system is 6.5 to 7.2, the hydrodynamic diameter of the nano-dispersed particles inside the additive is 80 nm to 300 nm, and the surface of the nanoparticles is coated with a composite hydration layer composed of phosphocholine and sulfobetaine.

[0008] A method for preparing an additive to inhibit polyphosphoric acid crystallization includes the following steps: Step 1: Prepare boron-modified crosslinked phosphorylated polyquasi-rotaxane; Step 2: Prepare poly(2-methacryloyloxyethyl phosphocholine)-b-poly(oligomeric polyethylene glycol methyl ether methacrylate) amphiphilic block copolymer; Step 3: Boron-modified crosslinked phosphorylated polyrotaxane, amphiphilic block copolymer, sulfobetaine zwitterionic stabilizer and deionized water are mixed in proportion, and then dispersed by stirring, ultrasonically assembled, pH adjusted and purified by filtration to obtain a highly stable polyphosphoric acid crystallization inhibitor.

[0009] Optionally, the specific preparation process of step 1 includes the following sub-steps: Step 11: Disperse α-cyclodextrin and polyethylene glycol with hydroxyl groups at both ends in deionized water, and stir at a constant temperature of 20℃~30℃ for 12~24h to obtain polyquasi-rotaxane inclusion complex slurry; Step 12: Add N,N-dimethylformamide solution containing triphenylchloromethane dropwise to the polyquasi-rotaxane inclusion complex slurry, react at room temperature for 20-28 h to cap the end hydroxyl groups of polyethylene glycol, and obtain capped polyquasi-rotaxane by precipitation, washing and drying; Step 13: Disperse the end-capped polyquasi-rotaxane in anhydrous pyridine, and simultaneously add phosphorus oxychloride and boric acid under nitrogen protection at 0℃~5℃. The temperature is raised to 35℃~45℃ and reacted for 5~7h. After hydrolysis, dialysis and freeze drying, boron-modified cross-linked phosphorylated polyquasi-rotaxane is obtained.

[0010] Optionally, in step 13, the molar ratio of phosphorus oxychloride to the exposed hydroxyl group of α-cyclodextrin is 1:3 to 1:5, the molar ratio of boric acid to the exposed hydroxyl group of α-cyclodextrin is 1:3 to 1:5, and the hydrolysis temperature is 20℃ to 30℃.

[0011] Optionally, the specific preparation process of step 2 includes the following sub-steps: Step 21: Using 4-cyano-4-(phenylthiocarbamoylthio)valerate as a chain transfer agent and azobisisobutyronitrile as an initiator, the oligomeric polyethylene glycol methyl ether methacrylate monomer is dissolved in 1,4-dioxane, degassed by freeze-thaw, and polymerized at 65-75℃ for 4-8 hours to prepare the poly(oligomeric polyethylene glycol methyl ether methacrylate) macromolecular chain transfer agent; Step 22: Poly(oligoethylene glycol methyl ether methacrylate) macromolecular chain transfer agent and 2-methacryloyloxyethyl phosphocholine monomer are dissolved in a water / ethanol mixed solvent, and 4,4'-azobis(4-cyanopentanoic acid) initiator is added. Polymerization is carried out at 65℃~75℃ for 5~7h. After dialyzing and freeze drying, an amphiphilic block copolymer is obtained.

[0012] Optionally, the process parameters for step 3 are as follows: the mixing environment is 20℃~35℃ in the dark. First, the boron-modified cross-linked phosphorylated polyquasi-rotaxane is added to deionized water and stirred at 400rpm~800rpm for 20~40min to form a uniform suspension. Then, the amphiphilic block copolymer and sulfobetaine zwitterionic stabilizer are added and stirred continuously for 50~70min. At the same time, the mixture is ultrasonically treated with a 100W~300W probe for 5~15min. The pH of the system is adjusted to 6.5~7.2. Finally, the mixture is filtered through a 0.45μm filter membrane to obtain the finished additive product.

[0013] In summary, the present invention has at least one of the following beneficial technical effects: This invention provides an additive for inhibiting polyphosphoric acid crystallization and its preparation method. Through the synergistic combination of boron-modified cross-linked phosphorylated polyquasi-rotaxane and sulfobetaine zwitterionic stabilizer, a multi-layered crystallization inhibition system is constructed, overcoming the technical bottleneck of traditional single-phase crystallization inhibitors. The boron-modified cross-linked structure forms a stable three-dimensional slip framework that can dynamically adapt to the growth state of polyphosphoric acid crystal faces, continuously passivating crystal face activity and inhibiting crystal development from the source.

[0014] The zwitterionic components can effectively shield the interference of ionic charges inside the aqueous solution, eliminate the driving force for crystal nucleus aggregation, and at the same time form a dense and stable hydration layer on the surface of the system, effectively preventing the deposition and aggregation of crystal particles.

[0015] It is suitable for a wide temperature range, is resistant to storage, and has no significant performance degradation. It can maintain the uniformity and stability of the polyphosphate aqueous solution system for a long time, completely solve the problems of pipeline blockage and performance degradation, and effectively ensure the long-term performance of polyphosphate fertilizer and flame retardant system. The process is simple and controllable, and it is suitable for industrial mass production and actual working conditions. Attached Figure Description

[0016] Figure 1 This is a schematic diagram comparing the crystallization induction time of Implementation Example 1 and Comparative Example 1 of the present invention; Figure 2 This is a schematic diagram comparing the crystallization induction time of Implementation Example 2 and Comparative Example 2 of the present invention. Detailed Implementation

[0017] The present invention will be further described in detail below with reference to the accompanying drawings.

[0018] This invention discloses an additive for inhibiting polyphosphoric acid crystallization and its preparation method.

[0019] Reference Figure 1 and Figure 2 Example 1, an additive for inhibiting polyphosphoric acid crystallization, comprising the following components by weight: 6-22 parts of boron-modified crosslinked phosphorylated polyquasi-rotaxane, 2-8 parts of amphiphilic copolymer containing phosphocholine blocks, 0.5-3 parts of sulfobetaine zwitterionic stabilizer, and 67-91.5 parts of deionized water. The phosphorylated polyquasi-rotaxane is a polyanionic slip ring compound with sliding elasticity obtained by ring encapsulation of α-cyclodextrin and polyethylene glycol chains, followed by end-capping and partial phosphorylation modification. The amphiphilic copolymer containing the phosphocholine block is a copolymer with an AB block structure, wherein the A block is poly(2-methacryloyloxyethyl phosphocholine) and the B block is poly(oligomeric polyethylene glycol methyl ether methacrylate). The sulfobetaine zwitterionic stabilizer is used to shield the solution charge, enhance hydration and water retention, and synergistically inhibit the formation of polyphosphate crystal nuclei and crystal growth.

[0020] By adopting the above technical solution, the additive, according to the weight ratio system, is composed of boron-modified cross-linked phosphorylated polyquasi-rotaxane, an amphiphilic copolymer containing phosphocholine blocks, a zwitterionic stabilizer of sulfobetaine, and deionized water. The proportions of each component are strictly adapted to the metastable characteristics of the polyphosphate aqueous solution, and can exert an inhibitory effect on multiple dimensions such as crystal growth, particle aggregation, and system stabilization.

[0021] Boron-modified crosslinked phosphorylated polyquasi-rotaxane, relying on the ring-entry structure of cyclodextrin and polyethylene glycol, combined with end-capping modification and phosphorylation modification, forms a multi-anionic framework structure with sliding elasticity. This structure can freely slide and adhere to the newly formed crystal faces in polyphosphoric acid solution, and passivate the crystal face activity through physical covering and charge adsorption, thus hindering the continuous stacking and growth of polyphosphoric acid molecules on the crystal face.

[0022] Amphiphilic copolymers containing phosphocholine blocks possess a typical block structure. The hydrophobic and hydrophilic segments work synergistically to spontaneously form micelle structures in solution, uniformly dispersing within the polyphosphoric acid system and preventing the aggregation of tiny crystal nuclei. Sulfobetaine, an amphoteric stabilizer, balances the free charge within the aqueous solution, weakening the nucleation-inducing effect of ionic polarization. Simultaneously, it forms a dense hydration layer on the particle surface, locking in water molecules and preventing localized supersaturation crystallization. This multi-component synergy achieves a long-lasting crystal-inhibiting effect.

[0023] Example 2, wherein the boron-modified crosslinked phosphorylated polyquadrane satisfies the following parameters: the number-average molecular weight of polyethylene glycol is 3000-8000, the molar ratio of α-cyclodextrin to the repeating ethylene oxide unit in polyethylene glycol is 1:2-1:4, the degree of phosphorylation substitution of α-cyclodextrin is 1.0-2.5, and the degree of boron crosslinking is 15%-30%.

[0024] By adopting the above technical solution, polyethylene glycol is selected within a specific molecular weight range, which can ensure that the molecular chain has appropriate flexibility and length. This can not only ensure the free sliding ability of cyclodextrin units on the molecular chain, but also avoid the problems of excessively long molecular chains entangled and agglomerated, and insufficient structural stability due to excessively short molecular chains.

[0025] The ratio of α-cyclodextrin to ethylene oxide repeating units determines the inclusion density of cyclodextrin in the system. A reasonable ratio ensures sufficient active modification sites, providing a structural basis for subsequent phosphoesterification and boron crosslinking modification. The degree of substitution during phosphoesterification controls the number of anions on the cyclodextrin surface. When the degree of substitution is within this range, the material's charge adsorption capacity is moderate, allowing for stable adherence to the crystal plane without causing solution flocculation instability due to excessive charge.

[0026] The degree of boron crosslinking is used to regulate the strength of the three-dimensional framework of quasi-rotaxane. A suitable degree of crosslinking can improve the rigidity and stability of the overall structure, effectively resist temperature fluctuations and solution ion impacts, ensure the long-term working capability of the slip passivation crystal plane, and avoid the defects of traditional quasi-rotaxane structures being easy to loosen and fail.

[0027] Example 3: The amphiphilic copolymer containing the phosphocholine block satisfies the following parameters: the mass ratio of poly(2-methacryloyloxyethyl phosphocholine) block to poly(oligoethylene glycol methyl ether methacrylate) block is 1:2 to 2:1, the number average molecular weight of the copolymer is 8000 to 30000, and the critical micelle concentration is 0.02 g / L to 0.08 g / L.

[0028] By adopting the above technical solution, the hydrophilic block is responsible for binding water molecules to form a hydration barrier layer, and the hydrophobic block is responsible for adsorbing tiny crystal nuclei. The balanced block ratio allows the copolymer to be evenly distributed in the aqueous system and the solid-liquid interface, achieving the best dispersion and barrier effect.

[0029] The appropriate molecular weight range of the copolymer ensures a suitable degree of molecular chain extension. Too low a molecular weight leads to insufficient micelle strength, failing to prevent crystal aggregation over a long period. Too high a molecular weight causes molecular entanglement and accumulation, affecting the system's flowability and dispersion uniformity. The critical micelle concentration parameter defines the minimum effective concentration of the copolymer. Within this parameter range, even trace amounts of the copolymer can stably form micelle structures in polyphosphoric acid solution, fully exerting its anti-deposition and anti-aggregation effects, making it suitable for long-term storage and transportation conditions.

[0030] Example 4: The zwitterionic stabilizer of sulfobetaine is N-sulfopropyl-N,N-dimethylbetaine with a purity of ≥98%, a water solubility of ≥500g / L at 25°C, and stable existence in aqueous solutions with pH values ​​of 4-9 while maintaining its zwitterionic structure.

[0031] By employing the above technical solution, the high-purity stabilizer can prevent impurity ions from introducing new crystal nucleation sites, ensuring the purity and stability of the polyphosphoric acid system. This stabilizer possesses extremely high water solubility, completely dissolving and dispersing uniformly in the aqueous phase without precipitation, and can comprehensively cover every interface of the solution system.

[0032] Meanwhile, this zwitterionic material possesses wide pH stability, maintaining a stable zwitterionic structure within the acid-base fluctuation range of conventional polyphosphoric acid solutions, continuously exerting charge neutralization and hydration-locking effects. By counteracting the polarization of free anions and cations in the solution, it eliminates the inductive driving force for crystal nucleation, reducing the number of microcrystalline nuclei of polyphosphoric acid from the source, and assisting the polymer system in achieving omnidirectional crystal suppression.

[0033] Example 5: The pH value of the additive system is 6.5-7.2, the hydrodynamic diameter of the nano-dispersed particles inside the additive is 80nm-300nm, and the surface of the nanoparticles is coated with a composite hydration layer composed of phosphocholine and sulfobetaine.

[0034] By adopting the above technical solution, the macroscopic performance and microscopic structure parameters of the additive finished product system are limited, the pH of the system is maintained in the neutral to slightly acidic range, and it is compatible with the original system of polyphosphate aqueous solution. It will not change the chemical properties and efficacy of polyphosphate itself, and can be directly adapted to the application scenarios of water fertilizer and flame retardant liquid.

[0035] The particle size range of the nano-dispersed particles ensures excellent dispersion and penetration of the additive. Nanoscale particles can penetrate deep into the interplanar spaces of polyphosphoric acid crystals, achieving omnidirectional crystal passivation without significantly increasing the system's viscosity or affecting solution flowability. The composite hydration layer formed on the particle surface combines the dual hydrophilic properties of phosphocholine and sulfobetaine, resulting in a dense and stable structure that can prevent crystal nucleus stacking and growth over a long period, effectively inhibiting crystal precipitation and pipeline deposition, and ensuring long-term storage stability of the system.

[0036] Example 6, a method for preparing an additive to inhibit polyphosphoric acid crystallization, comprising the following steps: Step 1: Prepare boron-modified crosslinked phosphorylated polyquasi-rotaxane; Step 2: Prepare poly(2-methacryloyloxyethyl phosphocholine)-b-poly(oligomeric polyethylene glycol methyl ether methacrylate) amphiphilic block copolymer; Step 3: Boron-modified crosslinked phosphorylated polyrotaxane, amphiphilic block copolymer, sulfobetaine zwitterionic stabilizer and deionized water are mixed in proportion, and then dispersed by stirring, ultrasonically assembled, pH adjusted and purified by filtration to obtain a highly stable polyphosphoric acid crystallization inhibitor.

[0037] By adopting the above technical solution, the overall process follows a step-by-step approach of monomer preparation followed by compounding and assembly, which logically aligns with the material structure forming rules. The core anti-crystallization matrix and the micellar stabilizing matrix are synthesized separately to ensure the structural integrity and performance stability of the two polymer materials, avoiding structural defects caused by a one-step compounding process.

[0038] The subsequent aqueous phase mixing, stirring, and ultrasonic assembly processes allow the components to be uniformly compounded at the molecular scale, forming a stable nano-dispersion system. pH adjustment and filtration purification steps remove trace impurities and unstable aggregates, improving the overall stability and uniformity of the additive. The entire process is clearly defined in steps and operates under mild conditions, without damaging the core functional structures of each component, enabling the stable preparation of composite additives with multiple anti-crystallization properties.

[0039] Example 7, the specific preparation process of step 1 includes the following sub-steps: Step 11: Disperse α-cyclodextrin and polyethylene glycol with hydroxyl groups at both ends in deionized water, and stir at a constant temperature of 20℃~30℃ for 12~24h to obtain polyquasi-rotaxane inclusion complex slurry; Step 12: Add N,N-dimethylformamide solution containing triphenylchloromethane dropwise to the polyquasi-rotaxane inclusion complex slurry, react at room temperature for 20-28 h to cap the end hydroxyl groups of polyethylene glycol, and obtain capped polyquasi-rotaxane by precipitation, washing and drying; Step 13: Disperse the end-capped polyquasi-rotaxane in anhydrous pyridine, and simultaneously add phosphorus oxychloride and boric acid under nitrogen protection at 0℃~5℃. The temperature is raised to 35℃~45℃ and reacted for 5~7h. After hydrolysis, dialysis and freeze drying, boron-modified cross-linked phosphorylated polyquasi-rotaxane is obtained.

[0040] By adopting the above technical solution, the inclusion stage involves constant temperature and long-term stirring, which allows cyclodextrin and polyethylene glycol molecules to fully penetrate and include each other, forming a uniform and stable quasi-rotaxane precursor slurry. This ensures that the inclusion structure is regular and consistent, providing a uniform matrix for subsequent modification.

[0041] End-capping can lock the structures at both ends of polyethylene glycol molecules, preventing cyclodextrin from slipping off the molecular chain and fixing the slippery functional structure, thereby improving the overall structural stability of the material. Low-temperature simultaneous modification can precisely control the phosphoesterification and boron crosslinking reaction rates, avoiding structural agglomeration caused by excessive local reactions, achieving uniform surface modification of cyclodextrin, and stably constructing a three-dimensional multi-anionic framework that combines slippery flexibility with structural rigidity.

[0042] In Example 8, in step 13, the molar ratio of phosphorus oxychloride to the exposed hydroxyl group of α-cyclodextrin is 1:3 to 1:5, the molar ratio of boric acid to the exposed hydroxyl group of α-cyclodextrin is 1:3 to 1:5, and the hydrolysis temperature is 20℃ to 30℃.

[0043] By adopting the above technical solution, the key ratios and temperature parameters of the boron-modified crosslinked phosphorylated polyquasi-rotaxane modification stage are limited. The ratio of the reaction reagent to the cyclodextrin hydroxyl group can be precisely controlled to control the degree of phosphorylation substitution and the degree of boron crosslinking, so that the modified material can take into account both charge adsorption capacity and structural stability.

[0044] A mild hydrolysis temperature ensures the stable hydrolysis and molding of the phosphate ester intermediate, avoiding structural breakage and functional group loss caused by high-temperature hydrolysis. This maximizes the preservation of the modified active functional groups and three-dimensional framework structure, ensuring that the finished quasi-rotaxane can stably exert its crystal passivation and dynamic crystal inhibition effects.

[0045] Example 9, the specific preparation process of step 2 includes the following sub-steps: Step 21: Using 4-cyano-4-(phenylthiocarbamoylthio)valerate as a chain transfer agent and azobisisobutyronitrile as an initiator, the oligomeric polyethylene glycol methyl ether methacrylate monomer is dissolved in 1,4-dioxane, degassed by freeze-thaw, and polymerized at 65-75℃ for 4-8 hours to prepare the poly(oligomeric polyethylene glycol methyl ether methacrylate) macromolecular chain transfer agent; Step 22: Poly(oligoethylene glycol methyl ether methacrylate) macromolecular chain transfer agent and 2-methacryloyloxyethyl phosphocholine monomer are dissolved in a water / ethanol mixed solvent, and 4,4'-azobis(4-cyanopentanoic acid) initiator is added. Polymerization is carried out at 65℃~75℃ for 5~7h. After dialyzing and freeze drying, an amphiphilic block copolymer is obtained.

[0046] By adopting the above technical solution, the polymerization process of amphiphilic block copolymers adopts a reversible addition-fragmentation chain transfer polymerization method. A uniform macromolecular chain transfer agent is first prepared to ensure the structural controllability of subsequent block polymerization and avoid the problems of uneven molecular structure and unstable performance caused by random polymerization.

[0047] Segmented polymerization allows for precise control of the ratio and molecular weight of the two blocks, ensuring a uniform distribution of hydrophilic and hydrophobic blocks. The resulting copolymer exhibits a well-defined micelle structure and excellent dispersion properties. The gentle polymerization temperature and purification process remove unreacted monomers and impurities, guaranteeing copolymer purity and enabling stable assembly into a barrier hydration layer in the aqueous phase, continuously inhibiting crystal particle aggregation and deposition.

[0048] Example 10, the process parameters for step 3 are as follows: the mixing environment is 20℃~35℃ in the dark. First, the boron-modified cross-linked phosphorylated polyquasi-rotaxane is added to deionized water and stirred at 400rpm~800rpm for 20~40min to form a uniform suspension. Then, the amphiphilic block copolymer and sulfobetaine zwitterionic stabilizer are added and stirred continuously for 50~70min. At the same time, the mixture is ultrasonically treated with a 100W~300W probe for 5~15min. The pH of the system is adjusted to 6.5~7.2. Finally, the mixture is filtered through a 0.45μm filter membrane to obtain the additive product.

[0049] By adopting the above technical solution, all process parameters for additive compounding and molding are limited. The light-proof, room-temperature mixing environment can avoid the aging and failure of polymer structures caused by light and high temperatures. The step-by-step feeding and stirring method first disperses the polymer matrix and then adds stabilizing components, which can avoid local agglomeration of components and achieve uniform dispersion of the system.

[0050] Ultrasonic-assisted assembly can utilize the cavitation effect to enhance intermolecular recombination and promote the formation of stable nanocomposite dispersion structures among the components. Precise pH adjustment and precision filtration can remove trace agglomerates and impurities from the system, stabilize the acid-base environment of the system, and ultimately obtain a uniformly dispersed, stable, and long-lasting anti-crystallization additive product, which is fully suitable for long-term storage and pipeline transportation of polyphosphate aqueous solutions.

[0051] The following specific embodiments illustrate the implementation principle of the present invention: Specific implementation case 1, the application scenario is the long-term storage and pipeline drip irrigation application of agricultural high-concentration liquid ammonium polyphosphate fertilizer.

[0052] Step 1: Preparation of boron-modified crosslinked phosphorylated polyquasi-rotaxane. 20 parts by weight of α-cyclodextrin and polyethylene glycol with hydroxyl ends and a number-average molecular weight of 6000 were dispersed in deionized water. The molar ratio of α-cyclodextrin to the repeating ethylene oxide units in polyethylene glycol was 1:3. The mixture was stirred at 25°C for 18 hours to obtain a polyquasi-rotaxane inclusion complex slurry. An N,N-dimethylformamide solution containing triphenylchloromethane was added dropwise to the slurry. The molar ratio of triphenylchloromethane to the terminal hydroxyl groups of polyethylene glycol was 2.5:1. The mixture was reacted at room temperature for 24 hours for end-capping. After precipitation, washing, and drying, the end-capped polyquasi-rotaxane was obtained. End-capped polyquasi-rotaxane was dispersed in anhydrous pyridine. Under nitrogen protection and at 2°C, a pyridine solution of phosphorus oxychloride and boric acid was added dropwise simultaneously. The molar ratio of phosphorus oxychloride to the exposed hydroxyl groups of α-cyclodextrin was 1:4, and the molar ratio of boric acid to the exposed hydroxyl groups of α-cyclodextrin was 1:4. The reaction was carried out at 40°C for 6 hours. After hydrolysis at 25°C, the mixture was dialyzed and freeze-dried to obtain boron-modified crosslinked phosphorylated polyquasi-rotaxane with a phosphorylation substitution degree of 2.0 and a boron crosslinking degree of 23%.

[0053] Step 2: Preparation of poly(2-methacryloyloxyethylphosphocholine)-b-poly(oligomeric polyethylene glycol methyl ether methacrylate) amphiphilic block copolymer. Using 4-cyano-4-(phenylthiocarbamoylthio)valerate as a chain transfer agent and azobisisobutyronitrile as an initiator, the oligomeric polyethylene glycol methyl ether methacrylate monomer was dissolved in 1,4-dioxane. After freeze-thaw degassing, polymerization was carried out at 70°C for 6 hours to obtain the poly(oligomeric polyethylene glycol methyl ether methacrylate) macromolecular chain transfer agent. This macromolecular chain transfer agent and 2-methacryloyloxyethylphosphocholine monomer were dissolved in a 1:1 volume ratio of water and ethanol. 4,4'-azobis(4-cyanopentanoic acid) initiator was added, and polymerization was carried out at 70°C for 6 hours. After dialysis and freeze-drying, the amphiphilic block copolymer was obtained. The copolymer has a number-average molecular weight of 18,000, a mass ratio of poly(2-methacryloyloxyethyl phosphocholine) block to poly(oligoethylene glycol methyl ether methacrylate) block of 1:1.5, and a critical micelle concentration of 0.05 g / L.

[0054] Step 3: By weight, in a light-protected environment at 25°C, add 14 parts of the boron-modified crosslinked phosphorylated polyquasi-rotaxane obtained in Step 1 to 81.5 parts of deionized water, and stir at 600 rpm for 30 min to form a uniform suspension. Then add 4 parts of the amphiphilic block copolymer obtained in Step 2 and 0.5 parts of N-sulfopropyl-N,N-dimethyl betaine, and continue stirring for 60 min, while simultaneously sonicating with a 200W probe for 10 min, with a 5-second sonication cycle. Adjust the pH of the system to 6.8 with 0.1 mol / L sodium hydroxide solution, and filter through a 0.45 μm filter membrane to obtain the finished additive. The hydrodynamic average diameter of the nano-dispersed particles in the finished product is 185 nm.

[0055] Comparative Example 1: Commercially available polycarboxylate scale inhibitors and dispersants are used, with the main component being sodium maleic acid-acrylic acid copolymer, a solid content of 40%, and a molecular weight of approximately 4500.

[0056] 2.5 parts by weight of the commercially available dispersant and 97.5 parts by weight of deionized water were stirred at 400 rpm for 20 min at room temperature and filtered through a 0.45 μm filter membrane to obtain the comparative additive.

[0057] Comparison of product testing results: The additive prepared in Specific Implementation Case 1 and the additive in Comparative Example 1 were added to an agricultural ammonium polyphosphate aqueous solution with a total phosphorus content of 37% at a dosage of 2000 mg / L, respectively. The results were compared under constant temperature storage conditions of 40℃. The comparison results are shown in Table 1. Table 1 Figure 1 This is a comparison of the crystallization induction time of the additive prepared in Specific Example 1 and the additive in Comparative Example 1 in an agricultural ammonium polyphosphate solution at 40°C. The figure directly shows that the crystallization induction time using the method of this invention is as long as 18.5 h, while that of the traditional polycarboxylate dispersant is only 3.2 h, representing an increase of nearly 5 times. This clearly demonstrates the significant delaying effect of the additive of this invention on the crystallization nucleation process.

[0058] The test data clearly demonstrates that the additive provided in Implementation Case 1 exhibits significantly superior performance compared to traditional polycarboxylate dispersants in inhibiting polyphosphate crystallization and maintaining long-term solution stability. Under accelerated storage conditions at 40°C, the ammonium polyphosphate solution with the traditional dispersant began to induce crystallization in just 3.2 hours, and visible precipitation appeared after 30 days. In contrast, this solution significantly extended the crystallization induction time to 18.5 hours, and the solution remained clear and transparent after 30 days. At the microscopic level, this solution drastically reduced the average crystal nucleus size from 1250 nm to 85 nm, effectively preventing the crystal nuclei from growing into large, precipitable particles. In pipeline filtration tests simulating real-world applications, the traditional solution in Implementation Case 1 became completely clogged after 60 days, while the pressure difference growth rate of this solution was only 12%, ensuring long-term pipeline patency. Furthermore, this solution also increased the effective phosphorus retention rate by 5.3 percentage points, reducing the loss of effective components caused by crystallization and precipitation. These data fully demonstrate the effectiveness and significant advancement of the dynamic slip passivation and composite hydration layer repulsion mechanism formed by the synergistic effect of boron-modified crosslinked phosphorylated polyquadrogenase, amphiphilic block copolymer, and sulfobetaine stabilizer.

[0059] Specific Implementation Case 2: The application scenario is an industrial coating-grade ammonium polyphosphate flame retardant treatment liquid, which needs to maintain a non-crystallized state for a long time under conditions of high solid content and high ionic strength.

[0060] Step 1: Preparation of boron-modified crosslinked phosphorylated polyquasi-rotaxane. 15 parts by weight of α-cyclodextrin and polyethylene glycol with hydroxyl ends and a number-average molecular weight of 4000 were dispersed in deionized water. The molar ratio of α-cyclodextrin to the repeating ethylene oxide units in polyethylene glycol was 1:2.5. The mixture was stirred at 22°C for 20 h to obtain a polyquasi-rotaxane inclusion complex slurry. An N,N-dimethylformamide solution containing triphenylchloromethane was added dropwise to the slurry. The molar ratio of triphenylchloromethane to the terminal hydroxyl groups of polyethylene glycol was 3:1. The mixture was reacted at room temperature for 26 h for end-capping. After precipitation, washing, and drying, the end-capped polyquasi-rotaxane was obtained. End-capped polyquasi-rotaxane was dispersed in anhydrous pyridine. Under nitrogen protection and at 1°C, a pyridine solution of phosphorus oxychloride and boric acid was added dropwise simultaneously. The molar ratio of phosphorus oxychloride to the exposed hydroxyl group of α-cyclodextrin was 1:5, and the molar ratio of boric acid to the exposed hydroxyl group of α-cyclodextrin was 1:3.5. The reaction was carried out at 38°C for 7 hours. After hydrolysis at 22°C, the mixture was dialyzed and freeze-dried to obtain boron-modified crosslinked phosphorylated polyquasi-rotaxane with a phosphorylation substitution degree of 1.6 and a boron crosslinking degree of 28%.

[0061] Step 2: Preparation of poly(2-methacryloyloxyethylphosphocholine)-b-poly(oligomeric polyethylene glycol methyl ether methacrylate) amphiphilic block copolymer. Using 4-cyano-4-(phenylthiocarbamoylthio)valerate as a chain transfer agent and azobisisobutyronitrile as an initiator, the oligomeric polyethylene glycol methyl ether methacrylate monomer was dissolved in 1,4-dioxane. After freeze-thaw degassing, polymerization was carried out at 68°C for 7 hours to obtain the poly(oligomeric polyethylene glycol methyl ether methacrylate) macromolecular chain transfer agent. This macromolecular chain transfer agent and 2-methacryloyloxyethylphosphocholine monomer were dissolved in a 1:1 volume ratio of water and ethanol. 4,4'-azobis(4-cyanopentanoic acid) initiator was added, and polymerization was carried out at 68°C for 7 hours. After dialysis and freeze-drying, the amphiphilic block copolymer was obtained. The copolymer has a number-average molecular weight of 25,000, a mass ratio of poly(2-methacryloyloxyethyl phosphocholine) block to poly(oligoethylene glycol methyl ether methacrylate) block of 1.8:1, and a critical micelle concentration of 0.03 g / L.

[0062] Step 3: By weight, in a light-protected environment at 28°C, add 20 parts of the boron-modified crosslinked phosphorylated polyquasi-rotaxane obtained in Step 1 to 71 parts of deionized water, and stir at 700 rpm for 25 min to form a uniform suspension. Then add 7 parts of the amphiphilic block copolymer obtained in Step 2 and 2 parts of N-sulfopropyl-N,N-dimethyl betaine, and continue stirring for 65 min, while simultaneously sonicating with a 250W probe for 12 min, with a 6-second sonication cycle and a 4-second pause. Adjust the pH of the system to 7.0 with 0.1 mol / L hydrochloric acid solution, and filter through a 0.45 μm filter membrane to obtain the finished additive. The hydrodynamic average diameter of the nano-dispersed particles in the finished product is 220 nm.

[0063] Comparative Example 2: A conventional organophosphate crystal modifier, specifically tetrasodium hydroxyethylidene diphosphonate, with an active ingredient content of 90% and a pH of 7.5, was used. 4.5 parts by weight of this organophosphate modifier were mixed with 95.5 parts by weight of deionized water and stirred at 500 rpm for 30 min at room temperature. The mixture was then filtered through a 0.45 μm filter membrane to obtain a comparative additive.

[0064] The additives prepared in Specific Implementation Case 2 and the additives in Comparative Example 2 were added to an industrial ammonium polyphosphate flame retardant treatment solution with a solid content of 50% at an addition amount of 2500 mg / L, and a comparative test was conducted under a constant temperature storage condition of 45°C.

[0065] The comparison results of product testing are shown in Table 2: Table 2 Figure 2 The graph shows a comparison of the crystallization induction time of the additive prepared in Specific Implementation Example 2 and the additive in Comparative Example 2 in an industrial coating-grade ammonium polyphosphate flame retardant treatment solution at 45°C. The graph clearly shows that the crystallization induction time of the present invention reaches 22.3 h, while that of conventional organophosphate crystallization modifiers is only 2.8 h, representing an improvement of approximately 7 times. This fully demonstrates that even under harsh conditions of high temperature and high solids content, the additive of the present invention can still effectively inhibit crystallization induction and ensure the long-term stability of the system.

[0066] The test data further validated the significant technical advantages of the additive provided by this invention under extreme high temperature and high solids content conditions. Compared with traditional organophosphate crystallization modifiers, the solution in Specific Example 2 significantly extended the crystallization induction time at 45℃ from 2.8h to 22.3h, an increase of nearly 7 times, and the solution remained clear after 60 days. Microscopic characterization showed that, compared with the traditional solution in Example 2, the average particle size of the crystal nuclei suppressed by this solution had increased to 1680nm, forming a large number of hard particles that could settle, while this solution effectively controlled the crystal nucleus size at 92nm, far below the visible light scattering and sedimentation thresholds. In terms of rheological properties, the traditional solution caused a sharp increase in system viscosity of 47.3% and a tendency to gel, which seriously affected the penetration and impregnation process of the flame retardant liquid into the fabric. The viscosity change rate of this solution was only 8.5%, which fully ensured the smoothness and uniformity of industrial coating processing, and the impregnation uniformity retention rate was as high as 98.2%. This strongly demonstrates that the ternary synergistic system of the dynamic slip ring multi-anionic skeleton, cell membrane-mimicking amphiphilic polymer, and zwitterionic stabilizer of the present invention has a stabilizing effect that cannot be achieved by existing technologies in resisting high temperature disturbances and high electrolyte concentration shocks.

[0067] The above are all preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape and principle of the present invention should be covered within the scope of protection of the present invention.

Claims

1. An additive for inhibiting polyphosphoric acid crystallization, characterized in that, By weight, the additives include the following components: 6-22 parts of boron-modified crosslinked phosphorylated polyrotaxane, 2-8 parts of amphiphilic copolymer containing phosphocholine blocks, 0.5-3 parts of sulfobetaine zwitterionic stabilizer, and 67-91.5 parts of deionized water. The phosphorylated polyquasi-rotaxane is a polyanionic slip ring compound with sliding elasticity obtained by ring encapsulation of α-cyclodextrin and polyethylene glycol chains, followed by end-capping and partial phosphorylation modification. The amphiphilic copolymer containing the phosphocholine block is a copolymer with an AB block structure, wherein the A block is poly(2-methacryloyloxyethyl phosphocholine) and the B block is poly(oligomeric polyethylene glycol methyl ether methacrylate). The sulfobetaine zwitterionic stabilizer is used to shield the solution charge, enhance hydration and water retention, and synergistically inhibit the formation of polyphosphate crystal nuclei and crystal growth.

2. The additive for inhibiting polyphosphoric acid crystallization according to claim 1, characterized in that, The boron-modified crosslinked phosphorylated polyquasi-rotaxane satisfies the following parameters: the number-average molecular weight of polyethylene glycol is 3000-8000, the molar ratio of α-cyclodextrin to the repeating ethylene oxide unit in polyethylene glycol is 1:2-1:4, the degree of phosphorylation substitution of α-cyclodextrin is 1.0-2.5, and the degree of boron crosslinking is 15%-30%.

3. The additive for inhibiting polyphosphoric acid crystallization according to claim 2, characterized in that, The amphiphilic copolymer containing the phosphocholine block satisfies the following parameters: the mass ratio of poly(2-methacryloyloxyethyl phosphocholine) block to poly(oligoethylene glycol methyl ether methacrylate) block is 1:2 to 2:1, the number average molecular weight of the copolymer is 8000 to 30000, and the critical micelle concentration is 0.02 g / L to 0.08 g / L.

4. The additive for inhibiting polyphosphoric acid crystallization according to claim 3, characterized in that, The zwitterionic stabilizer of sulfobetaine is N-sulfopropyl-N,N-dimethylbetaine, with a purity of ≥98%, a water solubility of ≥500g / L at 25℃, and stable existence in aqueous solutions with pH values ​​of 4–9 while maintaining its zwitterionic structure.

5. The additive for inhibiting polyphosphoric acid crystallization according to claim 4, characterized in that, The additive system has a pH value of 6.5 to 7.2, the hydrodynamic diameter of the nano-dispersed particles inside the additive is 80 nm to 300 nm, and the surface of the nanoparticles is coated with a composite hydration layer composed of phosphocholine and sulfobetaine.

6. A method for preparing an additive for inhibiting polyphosphoric acid crystallization as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Prepare boron-modified crosslinked phosphorylated polyquasi-rotaxane; Step 2: Prepare poly(2-methacryloyloxyethyl phosphocholine)-b-poly(oligomeric polyethylene glycol methyl ether methacrylate) amphiphilic block copolymer; Step 3: Boron-modified crosslinked phosphorylated polyrotaxane, amphiphilic block copolymer, sulfobetaine zwitterionic stabilizer and deionized water are mixed in proportion, and then dispersed by stirring, ultrasonically assembled, pH adjusted and purified by filtration to obtain polyphosphoric acid crystallization inhibitor additive.

7. The preparation method according to claim 6, characterized in that, The specific preparation process of step 1 includes the following sub-steps: Step 11: Disperse α-cyclodextrin and polyethylene glycol with hydroxyl groups at both ends in deionized water, and stir at a constant temperature of 20℃~30℃ for 12~24h to obtain polyquasi-rotaxane inclusion complex slurry; Step 12: Add N,N-dimethylformamide solution containing triphenylchloromethane dropwise to the polyquasi-rotaxane inclusion complex slurry, react at room temperature for 20-28 h to cap the end hydroxyl groups of polyethylene glycol, and obtain capped polyquasi-rotaxane by precipitation, washing and drying; Step 13: Disperse the end-capped polyquasi-rotaxane in anhydrous pyridine, and simultaneously add phosphorus oxychloride and boric acid under nitrogen protection at 0℃~5℃. The temperature is raised to 35℃~45℃ and reacted for 5~7h. After hydrolysis, dialysis and freeze drying, boron-modified cross-linked phosphorylated polyquasi-rotaxane is obtained.

8. The preparation method according to claim 7, characterized in that, In step 13, the molar ratio of phosphorus oxychloride to the exposed hydroxyl group of α-cyclodextrin is 1:3 to 1:5, the molar ratio of boric acid to the exposed hydroxyl group of α-cyclodextrin is 1:3 to 1:5, and the hydrolysis temperature is 20℃ to 30℃.

9. The preparation method according to claim 8, characterized in that, Step 2's specific preparation process includes the following sub-steps: Step 21: Using 4-cyano-4-(phenylthiocarbamoylthio)valerate as a chain transfer agent and azobisisobutyronitrile as an initiator, the oligomeric polyethylene glycol methyl ether methacrylate monomer is dissolved in 1,4-dioxane, degassed by freeze-thaw, and polymerized at 65-75℃ for 4-8 hours to prepare the poly(oligomeric polyethylene glycol methyl ether methacrylate) macromolecular chain transfer agent; Step 22: Poly(oligoethylene glycol methyl ether methacrylate) macromolecular chain transfer agent and 2-methacryloyloxyethyl phosphocholine monomer are dissolved in a water / ethanol mixed solvent, and 4,4'-azobis(4-cyanopentanoic acid) initiator is added. Polymerization is carried out at 65℃~75℃ for 5~7h. After dialyzing and freeze drying, an amphiphilic block copolymer is obtained.

10. The preparation method according to claim 9, characterized in that, The process parameters for step 3 are as follows: The mixing environment is 20℃~35℃ in the dark. First, the boron-modified cross-linked phosphorylated polyquasi-rotaxane is added to deionized water and stirred at 400rpm~800rpm for 20~40min to form a uniform suspension. Then, the amphiphilic block copolymer and sulfobetaine zwitterionic stabilizer are added and stirred continuously for 50~70min. At the same time, the mixture is ultrasonically treated with a 100W~300W probe for 5~15min. The pH value of the system is adjusted to 6.5~7.

2. Finally, the mixture is filtered through a 0.45μm filter membrane to obtain the finished additive product.